Antifouling potentials of Neopetrosia proxima from Southern Guimaras againts the marine diatom Navicula ramosissima, barnacle Balanus sp., and green mussel Perna viridis - Calapuan, Jean Ruiz (University of the Philippines in the Visayas, 2014)
Control of fouling particularly on ships hulls and piping systems are still few of major problems of marine industry. Fuling happens to almost all surfaces in the sea, but some marine organisms remain completely fouling free. Sponges are highly considered rich sources of potential antifouling active compounds for the paint industry. Antifouling potentials ofNeopetrosia proxima against settlements of marine diatom Navicula ramosissima, barnacle Balanus sp., and green mussel Perna viridis were investigated. Test concentrations of methanolic crude extracts of n. proxima showed significant differences on the average population growth of navicula ramosissima (ANOVA, a= 0.05) at 24 hours, 48 hours, 72 hours and 96 hours. Post hoc test revealed no significant differences among test concentration of sponge extracts agaonst diatom N. ramosissima at 24 hours and 48 hours. Howevr, at 72 hours and 96 hours , significant differences were showed only between test concentrations 1.0 ug/ml and 100.0 ug/ml. Dunnet's (a=0.05) test showed significant differences on the settlement density of diatom N. ramosissima between control and three test concentrations. Mean settlement densities of barnacles Balanus sp. showed significant differences at three (3) test concentrations of sponge extracts. In addition, Post Hoc tst revealed significant differences on the attachment rate of Balanus sp. . Meanwhile, Perna viridis exhibited sigificant differences among three (3) test concentrations (ANOVA, a=0.05). Mehtanolic extracts of N. proxima also manifest to be non-toxic to P. viridis. ence, this study shows that marine sponge N. proxima possesses an antifouling activity and defined potential to be developed as an effective antifouling compound.